2011
DOI: 10.1182/blood.v118.21.2675.2675
|View full text |Cite
|
Sign up to set email alerts
|

Final Results of the Phase II SAPHIRE Trial of Resminostat (4SC-201) in Patients with Relapsed/Refractory Hodgkin Lymphoma

Abstract: 2675 Background: Resminostat is an oral pan-histone deacetylase (HDAC) inhibitor that has shown anti-tumor activity in a broad panel of preclinical models and revealed a favorable safety and efficacy profile in a first-in-man phase I study in patients (pts) with various solid tumor types. Resminostat is currently in phase II clinical development in pts with hepatocellular carcinoma (HCC), colorectal carcinoma (CRC) and Hodgkin Lymphoma (HL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Of interest, belinostat, an inhibitor of HDAC class I and II enzymes, demonstrated clinical activity in a phase II study of 32 patients with recurrent or metastatic thymoma and thymic carcinoma (25). Evaluation of resminostat as monotherapy in a Phase II clinical trial of relapsed/refractory Hodgkin lymphoma patients after high dose chemotherapy and autologous hematopoietic stem cell transplantation has yielded encouraging results; in a heavily pre-treated group of patients (median of 6 prior lines of therapy), the reported objective response rate by an independent central review board in an interim analysis was 33% (11 of 33 evaluable patients) by the Cheson criteria with a clinical benefit rate of 55% (18 of 33 patients) (26, 27). Resminostat is also being developed in combination with sorafenib in hepatocellular carcinoma (28) and with standard FOLFIRI treatment in colorectal cancer (ClinicalTrials.gov NCT01277406).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, belinostat, an inhibitor of HDAC class I and II enzymes, demonstrated clinical activity in a phase II study of 32 patients with recurrent or metastatic thymoma and thymic carcinoma (25). Evaluation of resminostat as monotherapy in a Phase II clinical trial of relapsed/refractory Hodgkin lymphoma patients after high dose chemotherapy and autologous hematopoietic stem cell transplantation has yielded encouraging results; in a heavily pre-treated group of patients (median of 6 prior lines of therapy), the reported objective response rate by an independent central review board in an interim analysis was 33% (11 of 33 evaluable patients) by the Cheson criteria with a clinical benefit rate of 55% (18 of 33 patients) (26, 27). Resminostat is also being developed in combination with sorafenib in hepatocellular carcinoma (28) and with standard FOLFIRI treatment in colorectal cancer (ClinicalTrials.gov NCT01277406).…”
Section: Discussionmentioning
confidence: 99%
“…Resminostat is also being developed in combination with sorafenib in hepatocellular carcinoma (28) and with standard FOLFIRI treatment in colorectal cancer (ClinicalTrials.gov NCT01277406). Overall, emerging tolerability and efficacy data from these ongoing studies are promising and the final results are awaited (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic effects were observed when it was used in combination with melphalan, bortezomib and S-2209 [ 76 ]. In a Phase II SAPHIRE trial, resminostat was also tested in relapsed or refractory Hodgkin Lymphoma (HL) [ 77 , 78 ]. Assessment of disease status was carried out by computed tomography in combination with positron emission tomography (PET/CT).…”
Section: Different Classes Of Hdac Inhibitorsmentioning
confidence: 99%
“…Another alkenyl type small molecule HDAC inhibitor, Panobinostat, received FDA approval in 2015 for the treatment of patients with multiple myeloma [70]. The FDA approvals of belinostat and panobinostat opened an avenue for the exploration of alkenyl type drug candidates and subsequently, resminostat [199][200][201][202] and pracinostat [203][204][205] were identified that are now undergoing clinical stage investigation. Givinostat [206][207][208], abexinostat [209,210], AR-42 [211,212] and bisthianostat [213,214] represents the chemically related compounds bearing a more rigid phenylhydroxamic acid while quisinostat [215][216][217], nanatinostat [218,219] and fimepinostat [220] containing a more polar pyrimidinyl heteroaromatic EED-EZH2 protein-protein interaction (PPI) disruption leads to loss of H3K27me3-stimulated PRC2 activity and prevents H3K27 trimethylation, which ultimately leads to decreased tumor cell proliferation in EZH2-mutated and PRC2-dependent cancer cells.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%